Conclusion: Our North is uur South - Sclofsky, Sebastián (Police and state crime in the Americas, 2024)
In the last years of the nineteenth century, the Cuban poet and independence hero, José Martí, warned the continent about a new imperialism surging from the North. While praising many of the achievements of the United States, Martí also highlighted the many problems affecting the US, including its racism and inequalities, and the potential danger that US imperialism could pose to the American continent.